Early Implanon discontinuation and associated factors among Implanon women users visiting public health facilities, in Kembata zone of Southern Ethiopia: An institution based cross-sectional study - Beyene, Gemechu Nigusie; Assefa, Nega; Mokonnon, Taklu Marama; Ejigu, Habtamu Bekele; Yadeta, Tesfaye Assebe (Frontiers in Global Women's Health, 2022)
Background: Contraceptive practice, is basis of fertility which plays a significant role in minimizing maternal morbidity and mortality. Implanon is one of in effect long-acting contraceptive method which prevents pregnancy for three years. Early implanon discontinuation may result in many adverse reproductive health outcome. Hence, this study aimed to assess the magnitude early implanon discontinuation among implanon user women attending public health facilities in Kembata zone, Southern Ethiopia. Methods: An institutional-based cross-sectional study was conducted on to select 454 women who removed implanon from March 01 to 30, 2020. Simple random sampling techniques were used to select study participant. Data was collected by using pretested and structured questionnaire. Data was entered using Epi Data version-3.1 and exported to STATA V-16 for analysis. Descriptive analysis was done along with bivariate and multivariable regression to identify factors associated with early implanon discontinuation. Statistical significance was declared at P-value <0.05 along with 95% Confidence interval. Results: In this study, 438 women were interviewed, making response rate of 96.48%. Magnitude of early implanon discontinuation was 56.4%, 95% CI (51.6 - 61.2). Educational status being primary, AOR= (2.92 95% CI (1.56-5.46)), rural resident (AOR=1.76 CI= (1.06-2.92), History of modern contraceptive use (AOR=2.14, 95% CI (1.14, 4.03), not satisfied by service AOR=3.05 CI= (1.52-6.12) and experiencing side effect AOR=3.36, 95% CI (2.09-5.42), lack follow up for appointment after insertion (AOR: 2.17, 95% CI (1.18, 4.79 have shown association with early implanon discontinuation. Conclusion: This study indicated that magnitude of early implanon discontinuation was high. Women who experienced side effect, rural resident, being not satisfied with service and rural resident showed association with implanon discontinuation. Family planning service provider should give attention to pre- insertion counselling about implanon side effect. Recognizing modifiable factors like, improving client’s service satisfaction, follow up and quality family planning service provision are the recommended intervention.